Levantamento das necessidades de capacitação dos servidores técnico-administrativos em educação lotados na pró-reitoria de gestão de pessoas da Universidade Federal de Santa Maria (UFSM) - Matte, Luciane Ines (2014)
The aim of this paper was to identify the main criteria used for the selection of training courses of the Department of Human Resources of the Federal University of Santa Maria Brazil; to find out which are the training programs offered to staff members; to identify the way the policy on training has been managed, considering the institution s reality, and, besides, to identify which training courses are more suitable for technical and administrative staff in education from Department of Human Resources. This way, the present study aimed at to apply a model for the mapping of training needs of technical and administrative staff in education working at the Department of Human Resources of the Federal University of Santa Maria. For this, at first it was sought to identify the factors that define the offer of training courses to the technical and administrative staff in education from the Department of Human Resources. The collection of data necessary for the accomplishment of this study was made through the application of a questionnaire, which was divided into three parts according to the aims to be achieved. They are: to analyze the organization (comprising seventeen questions); to analyze the tasks developed by the technical and administrative staff in education (comprising nine questions) and to analyze the profile of staff members (comprising twenty-one questions). It was also used a table including the names of the training courses arranged into three thematic areas, aiming at identifying which of them are the most sought by staff members. Furthermore, it was held an interview with managers of the Department of Human Resources, seeking to gather information about the people management policy adopted by the Department of Human Resources, as well as observations in loco. The results show that the Federal University of Santa Maria follows the guidelines suggested in the Mapping of the Training Needs, but they also indicate that there many gaps regarding the training courses offered. Staff members in general evaluated the institution well, but they pointed out an inefficient distribution of relevant information concerning the organization. On the other hand, they assume that the Federal University of Santa Maria has a good ability to supply services and products that are suitable for the market where it operates. Relating to the training courses, the ones that most meet the needs of Department of Human Resources staff are, respectively, Portuguese Language and Official Writing, Quality Service and Public Administration because they attained the highest scores in the evaluation.